Metaheuristics for The Solution of Dynamic Vehicle Routing Problem With Time Windows (DVRPTW) With Travel Time Variable - Nurlita Gamayanti; Abdullah Alkaff; Ahmad Rusdiansyah (Department of Electrical Engineering ITS and FORTEI, 2017)
This research is focusing on the development of metaheuristic algorithm to solve Dynamic Vehicle Routing Problem With Time Windows (DVRPTW) for the service provider of Inter-city Courier. The algorithm is divided into two stages which is static stage and dynamic stage. In the static stage, modified Ant Colony System is developed and in the dynamic stage, Insertion Heuristic is developed. In DVRPTW, vehicle’s routes are raised dynamically based on real time information, for example the reception of new order. To test the performances of the developed metaheuristic algorithm, the author compares the developed algorithm with the nearest neighbor algorithm and with the combination between the nearest neighbor and insertion heuristics algorithm. Experiment is done using Chen’s standard data test. The developed metaheuristic algorithm was applied on the network data of the roads in Surabaya, where the routes generated not only determine the order that the consumer must visit but also determine the routes that must be passed. After the experiment, the author conclude that the developed algorithm generates a better travel time total than the nearest neighbor and the combination between the nearest neighbor and insertion heuristics and can also generate route dynamically to respond to the new order well. Keywords: Inter-City Courier, Dynamic Vehicle Routing Problem dengan Time Window (DVRPTW), Ant Colony System, Insertion Heuristics